### Chap 4 (Recap 2) Let's TALK Algebra before the test ^.^

Let m denote Jane's present age in years.
Write an algebraic expression for each of the following:
(a) Twice Jane's age next year.
(b) Four times Jane's age 3 years ago.
(c) The present age of Jane's mother if her mother is now twice as old as Jane will be 3 years from now.

1. a) 2m+2

b) 4m-12

c) 2m+3

2. a) 2(m+1)=2m+2

b)4(m-3)=4m-12

c)2(m+3)=2m+6

3. a)2 x m+2=2m+2
b)3 x m-3=3m-3
c)2 x m+3=2m+3

4. sorry c) should be 2m+6

5. (a) (m+1) x 2 = 2m + 2
(b) (m-3) x 4 = 4m - 12
(c) (m + 3) x 2 = 2m + 6

JJ(:

6. a)2 x m + 2 x 1= 2m+2 years old (ANS)
b)4 x m+ 4 x 3= 4m+12 years old (ANS)
c) (m+ 3)2 = 2m +6 years old (ANS)

7. Here's the complete working and explanation:

(a)Twice Jane's age next year:
Next year, Jane's age will be m+1
So, twice Jane's age will be 2 times (m+1)
Therefore, 2(m+1) = 2m+2

(b) Four times Jane's age 3 years ago:
Jane's age 3 years ago was m-3
So, four times of that would be 4 times (m-3)
Therefore, 4(m-3) = 4m-12

(c) The present age of Jane's mother if her mother is now twice as old as Jane will be 3 years from now:
Jane's age 3 years from now would be m+3
Twice as old will be 2 times m+3
Therefore, 2(m+3) = 2m+6

1st level working is necessary to show we understand the statement, something like what Jing Jie and Joshua Ma had shown.

Joshua Loh: Note that you'll have to write down the brackets for m+2, m-3 and m+3. Also check the expressions again.